Incidental Appendiceal Carcinoids: A Rare Case at an Uncommon Site - Sharma, Sujan; Makaju, Ramesh; Rajbhandari, Nripesh (Annals of Clinical Chemistry and Laboratory Medicine, 2015)
We report a case of 10-year-old female, who was admitted in the surgical department of Dhulikhel Hospital with symptoms of acute appendicitis. The appendectomy was performed. The gross appearance of the appendix was of a slight catarrhal appendicitis, with no sign of a tumor, but the tip of the appendix was perforated. The histopathological examination revealed a carcinoid tumor on the tip of the appendix. No vascular or perineural invasion was seen. Conclusions: The appendectomy is enough for carcinoid tumors of the tip of the appendix, of small sizes, without vascular or perineural invasion.